Insurance and sustainability in flood‐risk management: the UK in a transitional state. Issue 3 (22nd July 2013) - Ball, Tom; Werritty, Alan; Geddes, Alistair
<x xml:space="preserve">Abstract</x> The emerging new paradigm of 'sustainable flood‐risk management', emphasising non‐structural management approaches over engineered defences, is subject to differing, and sometimes contested, interpretations by key actors. This is well illustrated by the present lack of agreement between the UK government and the private insurance sector on the future of flood insurance. This paper examines the diversity of views on how best to manage flood risk, given projected changes in the UK insurance market. The issues examined comprise: the linkage of flood defences to the insurability of properties at risk, possible implications of partial or full removal of cross‐subsidisation of policies, and the sustainability of communities in high flood‐risk areas. Finally, the paper looks critically at alternative models that might be applied in the future, based on international experience, which may offer a means of securing insurance for high flood‐risk areas, while also being compatible with sustainable flood‐risk management policies.